Biogas production through syntrophic acetate oxidation and deliberate operating strategies for improved digester performance. (1st October 2016) - Westerholm, Maria; Moestedt, Jan; Schnürer, Anna
Graphical abstract: Highlights: Syntrophic acetate oxidation (SAO) dominates in ammonia-adapted biogas processes. SAO bacteria compete for acetate and depend on their methanogenic partner. Syntrophic acetate oxidisers are present under a wide range of operating conditions. Ammonia, acetate, temperature, retention time and trace elements influence SAO. Awareness of SAO enables strategies for process optimisation. Abstract: Anaerobic degradation of protein-rich materials has high methane potential and produces nutrient-rich residue, but requires strategies to avoid ammonia inhibition. A well-adapted process can cope with substantially higher ammonia levels than an unadapted process and analyses of pathways for methanisation of acetate, combined with determination of microbial community structure, strongly indicate that this is due to a significant contribution of syntrophic acetate oxidation. The microorganisms involved in syntrophic acetate oxidation thus most likely occupy a unique niche and play an important role in methane formation. This review summarises current insight of syntrophic acetate oxidising microorganisms, their presence and the detection of novel species and relate these observations with operating conditions of the biogas processes in order to explore contributing factors for development of an ammonia-tolerant microbial community that efficiently degrades acetate through the syntrophic pathway. Besides high ammonia level, acetate concentration, temperature and methanogenic community structure are considered in this review as likely factors that shape and influence SAO-mediated microbial ecosystems. The main purpose of this review is to facilitate process optimisation through considering the activity and growth of this key microbial community.